BENTUK KOSAKATA BAHASA INGGRIS PADA MEDIA SOSIAL LEMBAGA PEMERINTAH INDONESIA - Adinda Prasty Ascalonicawati; Hayatul Cholsy (Prasasti: Journal of Linguistics)
Many exposure of foreign languages, in this case is English, in daily communication could give significant impact towards oral and written language to the Indonesian speech community. That phenomenon was the result of language contact which is widespread in this digital era. This research aimed to identify English vocabulary which found in the caption on social media Instagram account of Ministry and Non-Ministerial Government Agencies in Indonesia. Data in this research were the English loanwords vocabulary and interference which are obtained by applying observation method with screenshot and note taking technique. Data source used is the social media Instagram account of Ministry and Non-Ministerial Government Agencies in Indonesia, such as @bekrafid, @kemdikbud.ri, @ristekdikti, @kemlu.ri, @kemenpar, @infobmkg, and @kemenhub151. The results found of this study were loanwords, loanblends, and loanshifts, also phonological, morphological, and lexical interference.